[Gábor Radnai 3]
look-out tower on the "János-hegy", Pioneer railway, Balaton, children playing, in the garden of the weekend-house, cooking in stew-pot, tents, travelling with ship, Tihany, Badacsony, rainbow, shooting with air rifle,